Planteamientos intervencionistas en el discurso y en el análisis económico en Valencia, 1939-1951 - Gómez Herráez, José María (Millars. Espai i Història, 2018)
This article is an approach to the economic thoughts in Valencia during the 1939-1951 period. In order to carry out this task, observations through political speeches, Organización Sindical meetings, and technical studies are made. Aside from propaganda and triumphal considerations, the evolution of criticism towards the economic liberalism and the government role is analysed. The article focuses the influence den ved from the arguments of the Classical School and Keynesians in technical studies. The idea of the government interventionism is base on its role as a market regulator without considering the ossibility of encouraging deep structural changes.